In search of the Unicorn? Interdisciplinarity in Intellectual History. - López-Sánchez, Rosario (Taylor & Francis, 2019)
The aim of this paper is to reflect on the identity of intellectual history as an interdisciplinary field. It begins by taking into account the pervasiveness of interdisciplinarity in academia. As a trend embraced by many scholars and institutions, the paper argues that interdisciplinarity deserves to be thematised more specifically, since the literature swings between a wide range of definitions and fierce criticisms. Interdisciplinarity has been understood as a way to integrate specialized knowledge to better understand a topic, but this definition does not clarify how object of study determines the purposes of interdisciplinarity. As regards intellectual history, this essay offers a non-exhaustive but representative survey that throws light on the different and often contradictory ways in which intellectual history has been conceived as interdisciplinary. The paper ends by suggesting a way of fleshing out the commonplace that intellectual history is ‘inherently interdisciplinary.’ Following John Pocock and John Burrow, I take a pragmatic standpoint: to embrace interdisciplinarity whenever it helps us solve the problems that concern intellectual historians, and it help us navigate historical realities. And conversely, being aware that interdisciplinarity is not a good in itself, and it does not necessarily guarantee results that are historically accurate.
https://openpolicyfinder.jisc.ac.uk/id/publication/35140
Keywords: Vida intelectual; Intellectual history; Interdisciplinary